SYSTEMATIC LITERATURE REVIEW (SLR) IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Saputri, Shelvia Oktavianita; Eko Handoyo; Hanafi Hussin; Indriana Eko Armaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is a crucial aspect of elementary school learning in Indonesia, yet its implementation still faces various challenges, particularly in integrating local wisdom values into the learning process. This study aims to analyze the strategies, methods, and impacts of implementing local wisdom-based character education in elementary schools. This research employed a Systematic Literature Review (SLR) method by collecting, selecting, and analyzing relevant articles from various reputable journal databases following the PRISMA procedure. The selection process resulted in several articles that met the inclusion criteria and were relevant to the research topic. The findings reveal that the implementation of local wisdom-based character education in elementary schools is carried out through several strategies, including the integration of local cultural values into learning materials, the use of local stories and folklore as learning media, habituation of local traditions in school activities, and collaboration between schools and communities. Teachers play a significant role as facilitators and role models in instilling character values derived from local wisdom. The impact of this implementation shows positive results on students' behavior, moral development, and cultural identity preservation. Students demonstrate improvements in discipline, mutual respect, cooperation, and appreciation of their local culture. This study concludes that local wisdom-based character education is an effective approach for developing students' character in elementary schools and recommends continuous development and adaptation to the local context of each region